OPTIMASI KONSENTRASI L-Cysteine PADA MODIFIKASI SINTESIS NANOPARTIKEL PERAK (AgNPs) DENGAN L-Cysteine - Nisaul, Cindi Fitria; Alimuddin, Alimuddin; Arif, Moh. Syaiful (Jurusan Kimia FMIPA UNMUL, 2023)
Modification of synthesis of nanoparticles with L-Cysteine functions as a capping agent/stabilizer, so that the nanoparticles can last longer. Modification of nanoparticle synthesis by adding L-Cysteine to AgNPs and homogenizing it using a magnetic stirrer. Modification of nanoparticles (AgNPs) was monitored by observing the visible uptake. The results showed that the absorbance value increased by indicating the concentration of L-cysteine 5×10-5; 6×10-5; 7×10-5; 8×10-5; 9×10-5; 1×10-4 and the volume of L-cysteine is 4 mL.